2002
DOI: 10.1017/s0022029902005393
|View full text |Cite
|
Sign up to set email alerts
|

Influence of selected factors on browning of Camembert cheese

Abstract: Experimental Camembert cheeses were made to investigate the effects on browning of the following factors: inoculation with Yarrowia lipolytica, the use of Penicillium candidum strains with different proteolytic activity, the addition of tyrosine, and the addition of Mn2+, thus leading to 16 different variants of cheese. Two physical colour parameters were used to describe browning, depending on the location in the cheeses: a whiteness index for the outside browning (mould mycelium), and a brownness index for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Additionally, Chisari et al (2007) [ 46 ] reported that the POD enzyme also affected the browning of fresh-cut melon. In this study, the observed total phenol contents and the results of a KEGG analysis revealed that three PPO genes (Unigene0015096, Unigene0043875, and Unigene0015096) and one POD gene (Unigene0011770) related to the tyrosine metabolism pathway were differentially expressed while the phenolic acid (i.e., gallic acid) content increased in fresh-cut luffa fruit slices ( S4 Table ) [ 49 , 50 ]. The production of phenolic acids, including gallic acid, L-tyrosine, chlorogenic acid, and gentisic acid, catalyzed by browning-related enzymes (i.e., PPO and POD) can be affected by the tyrosine metabolism pathway [ 51 – 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chisari et al (2007) [ 46 ] reported that the POD enzyme also affected the browning of fresh-cut melon. In this study, the observed total phenol contents and the results of a KEGG analysis revealed that three PPO genes (Unigene0015096, Unigene0043875, and Unigene0015096) and one POD gene (Unigene0011770) related to the tyrosine metabolism pathway were differentially expressed while the phenolic acid (i.e., gallic acid) content increased in fresh-cut luffa fruit slices ( S4 Table ) [ 49 , 50 ]. The production of phenolic acids, including gallic acid, L-tyrosine, chlorogenic acid, and gentisic acid, catalyzed by browning-related enzymes (i.e., PPO and POD) can be affected by the tyrosine metabolism pathway [ 51 – 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of ripening on the color properties of the cheeses (Table 4), a significant reduction in L* and the a* coordinate were observed, whereas the b* coordinate value increased over time, possibly related to proteolysis and browning reactions that occur during maturation (Carreira et al, 2002;Tejada et al, 2007). A significant interaction (antibiotic concentration × ripening time, P < 0.001) was found for the a* coordinate, which was only significantly lower in SM cheeses with cloxacillin at 60 d of ripening.…”
Section: Color Evaluation Of the Cheesesmentioning
confidence: 99%
“…The pyomelanin pigment responsible for this discoloration defect is thought to be formed by the extracellular auto-oxidation of the tyrosine catabolite, homogentisic acid (Carreira et al, 2001;Williams & Withers, 2007). However, some conflicting observations were also made: (i) in studies on Camembert cheese, when used in combination with Penicillium candidum, Y. lipolytica either had no effect or even reduced browning (Carreira et al, 2002), (ii) Candida famata, rather than Y. lipolytica, was reported to be responsible for the production of a brownish pigment by van den Tempel & Jakobsen (1998), and (iii) although counts of Y. lipolytica in cottage cheese increased toward the end of the shelf life, this yeast was not identified in the visible spoilage area of the cheese (Brocklehurst & Lund, 1985). Thus, if Y. lipolytica indeed contributes to discoloration defects, it is safe to conclude that this trait displays pronounced strain-specific differences (Ross et As indicated by the balance, it will be crucial for a potential commercial application in the ripening of cheese or fermented meat products to favor the intended beneficial effects while suppressing the potential objectionable side effects of Yarrowia lipolytica.…”
Section: Natural Occurrence Of Yarrowia Lipolytica In Foodmentioning
confidence: 99%